The Belief about Medicines among a Sample of Iraqi Patients with Rheumatoid Arthritis - Faiq, Mirna K.; J. Kadhim, Dheyaa; I. Gorial, Faiq (Iraqi Journal of Pharmaceutical Sciences, 2019)
Rheumatoid arthritis is a chronic, progressive, inflammatory autoimmune disease of unidentified etiology, associated with articular, extra-articular and systemic manifestation that require long-standing treatment. Taking patient’s beliefs about the prescribed medication in consideration had been shown to be an essential factor that affects adherence of the patient in whom having positive beliefs is an essential for better adherence. The purpose of the current study was to measure beliefs about medicines among a sample of Iraqi patients with Rheumatoid arthritis and to determine possible association between this belief and some patient-certain factors. This study is a cross-sectional study carried out on 250 already diagnosed rheumatoid arthritis patients who attended to Baghdad Teaching Hospital/Medical City/Rheumatology department. The mean age of the patients was (50.8 ± 13.1 years). Belief about medicines was measured via the Arabic version of the Beliefs about Medicines Questionnaire. The majority of the patients (88%) had strong beliefs in the necessity of treatment (specific-necessity score greater than specific-concern). There was a significant direct correlation between age, male gender, number of other chronic disease, disease activity score 28 and clinical disease activity index with specific necessity, and direct correlation between clinical disease activity index with specific concern. Future studies should investigate how interventional approaches addressing these predictors may lead to improve beliefs about medicines among rheumatoid arthritis patients and their impression on disease control.